Scaffold to Build and Sustain industry-University Partnerships - Morell, Lueny (Journal of Engineering Education Transformations, 2014)
One of the most difficult tasks for higher education leadership is to initiate and sustain industry partnerships. There are many reasons why. A particular one is that industry and academia have different cultures and values. This paper provides a scaffold or framework to engage with the productive sector and provides answers to some of the questions involved: Why do higher education, institutions need to reach out to industry? Who needs to be involved? What can each of the partners’ roles, responsibilities and expectations be? How can industry help academia in strategizing to better educate the engineering workforce the country/region need? How to best approach industry? What are the benefits for the institution, industry, students and faculty of strong industry-university relationships? How to assess partnership outcomes? Finally, the author shares her experiences in participating and catalyzing three successful partnerships between industry and academia: the Learning Factory, the ASEE-NSF Industry Post Docs Program and the NEU@UNH, a new engineering education platform developed in California.